The Streetscapes Project : reflective paper - Ebrahim, Zakiyah (Centre for Film and Media Studies, 2017)
The Streetscapes Project is a photographic and journalistic documentation of ten street-based people's stories from Cape Town, South Africa. The subjects of the project are employed by Khulisa Social Solutions, a non-profit organisation (NPO) that adopts a systemic approach to breaking the cycle of crime and poverty. Streetscapes falls under two of the NPO's eleven programmes, i.e. the offender rehabilitation & reintegration programme and the diversion programme, and includes five social enterprises with the urban garden project in Roeland Street, Cape Town, being one of it. Through narratives and research this project shows how street-based people are highly motivated to work and rebuild their lives, and that having a job means more than simply earning an income to them – it provides them with self-worth, dignity and a source of hope. Beyond the documentation of their personal stories the project also explores the larger structural and systemic barriers surrounding the broader issue of homelessness in the city, including access to shelter services, among others. Ultimately, this project aims to debunk stereotypes about street-based people and enlighten the public about the challenges they face when living on the streets.